A NEW LOOK AT POETIC REQUIREMENTS AND A CREATIVE ATTITUDE - Pari Pashayeva (World Scientific Reports, 2023)
The period of time, starting from the 60s of the last century until the period of independence of Azerbaijan, played a significant role in the development of the socio-political worldview of our people and the creation of spiritual history. Revolutionary processes in society moved the thinking of the people, gave a powerful impetus to the mobilization of spiritual forces for more independent ideals. The strengthening of the processes of democratization and Publicity shed light on the dark pages of history, which ultimately led to the formation of critical attitudes towards reality in the minds of the people. Political debates taking place in the public environment accelerated the process of self-knowledge of the people and prepared a real basis for the spirit of freedom and the expansion of the movement for national independence. Acute social processes influenced the level of maturity in poetic thinking, in the views of creative literary forces, imperceptibly expanding the horizons of fiction, including poetry, which is one of the forms of figurative cognition of being. In the 1960s and 80s, Azerbaijani poetry gained important qualities and entered a period of new reforms. The renewal in the content and directions of our poetry, which reflects the person, his spiritual world, character, people’s spirit against the background of specific historical conditions and social processes, brought intensity to the improvement of its main poetic principles, to move away from a number of dogmas of the totalitarian regime by adopting new qualities.